PENGARUH TINGKAT IQ, SIKAP DAN IKLIM SEKOLAH TERHADAP HASIL BELAJAR EKONOMI SISWA - Yuli Dwi Khairani; Eddy Purnomo; Tedi Rusman (JEE (Jurnal Edukasi Ekobis), 2013)
This research was aimed to determine the factors affecting the students’ learning outcomes in the economy class in grade XI social studies of Senior High School 3 Bandar lampung that was limited to the IQ level of independent variable, the attitude of the subject, and school climate. The method used was the Ex Post Facto and Survey by using descriptive verification research design. Sampling is probability sampling technique and calculated by The T Yamane formula. The units of analysis were simple linear regression and multiple. The object was the students of grade XI social studies. Based on the data analysis calculated by using the statistic formula gained: (1). There was an influence of IQ level on learning outcomes. (2). There was an influence of attitudes on learning outcomes. (3). There was a school climate effects on learning outcomes. (4). There was an influence of IQ levels, attitudes, and school climate on learning outcomes.Penelitian ini bertujuan mengetahui faktor yang mempengaruhi hasil belajar ekonomi siswa kelas XI IPS SMA Negeri 3 Bandar lampung yang dibatasi variabel bebas tingkat IQ, sikap tentang mata pelajaran, dan iklim sekolah. Metode yang digunakan adalah Ex Post Facto dan Survey desain penelitian deskriptif verifikatif. Teknik samplingnya adalah probability sampling dengan simple random sampling dan perhitungannya menggunakan rumus T yamane. Unit analisis yaitu regresi linier sederhana dan multiple. Obyek adalah siswa XI IPS. Berdasarkan analisis data yang dihitung menggunakan rumus stasistik diperoleh: (1). Ada pengaruh tingkat IQ terhadap hasil belajar. (2). Ada pengaruh sikap terhadap hasil belajar. (3). Ada pengaruh iklim terhadap hasil belajar. (4). Ada pengaruh tingkat IQ, sikap, dan iklim sekolah terhadap hasil belajar.Kata kunci: hasil belajar, iklim sekolah, IQ, sikap.